Acculturation strategies of Chinese students in Indonesia - Yanrenjing, Chen; Kutanegara, Pande Made (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2021)
This article tries to analyze the acculturation process and acculturation strategies of Chinese students in Indonesia, particular in Yogyakarta. In recent years, the number of Chinese students studying abroad has increased rapidly, and Indonesia has also become one of the destinations. In response to the call of the “One Belt, One Road” policy, Chinese universities have established Indonesian language majors. More and more Chinese students come to Indonesia as exchange students, and at the same time are experiencing the process of acculturation. This research uses Yogyakarta as a research base and aims to propose strategies for the acculturation of Chinese students in Yogyakarta. The research uses ethnographic methods; literature reviews, participant observation, and structured interviews for data collection. The study found that in the early period, Chinese students had quite a lot of difficulty in adapting and acculturating with local people and culture. In the process of adaptation, Chinese students should improve the initiative of acculturation, cultivate new ideas and value systems, and learn to enjoy Indonesian customs.